Influence of neutral and stability athletic footwear on lower extremity coordination variability during a prolonged treadmill run in male rearfoot runners. Issue 6 (2nd July 2020) - Weir, Gillian; Wyatt, Hannah; Van Emmerik, Richard; Trudeau, Matthieu B.; Willwacher, Steffen; Brüggemann, Gert-Peter; Hamill, Joseph
ABSTRACT: The purpose of this study was to investigate changes in coordination variability (CV) over the course of a prolonged treadmill run and the influence of stability and neutral footwear on CV. Fourteen male habitually rearfoot runners completed two 42 min prolonged running sessions while three-dimensional kinematics and kinetics were recorded. During the first 21 min, participants ran in a neutral shoe (baseline run), then changed into either another neutral shoe of the same construction but another colour or a stability shoe and ran a further 21 min (intervention run). A modified vector coding technique was used to compute thigh-leg, leg-rearfoot and rearfoot-forefoot segment CV. Following the baseline run, thigh flexion/extension-leg flexion/extension, rearfoot inversion/eversion-forefoot plantar flexion/dorsiflexion and rearfoot inversion/eversion-forefoot adduction/abduction CV increased ( p  < .05). During the intervention run, CV was higher in the neutral shoe compared with the stability shoe for thigh flexion/extension-leg flexion/extension and leg flexion/extension-rearfoot inversion/eversion couplings ( p  < .05). Lower extremity CV increased or was maintained during a prolonged treadmill run in healthy male rearfoot runners, likely to distribute stresses among the tissues as muscles begin to fatigue. CV increased to a greater extent in neutral compared with stability footwear which may be a result of: (1) the stability shoe acting as a perturbation to the runner and their response is to regulate CV, or; (2) stability footwear provides greater support and consequently, runners do not need to explore additional degrees of freedom to reduce stresses applied to the tissues throughout a prolonged run.